Bilateral subconjunctival hemorrhage secondary to abciximab use: case report - Kul, Selim; Sayın, Muhammet Raşit (São Paulo Medical Journal, 2019)
CONTEXT: There are no reports on cases of subconjunctival hemorrhage due to use of glycoprotein IIb/IIIa inhibitors. In this report, we present the case of a patient with bilateral subconjunctival hemorrhage after receiving abciximab. CASE REPORT: A 40-year-old male patient underwent coronary angiography after acute anterior myo-cardial infarction and a coronary stent was placed. Abciximab was added to the therapy because of stent thrombosis. Bilateral subconjunctival hemorrhage was observed after the administration of the abciximab treatment. We treated our patient by stopping abciximab and administering artificial tears. CONCLUSİON: For the first time in the literature, we presented the case of a patient with bilateral subcon-junctival hemorrhage after receiving abciximab, which was managed conservatively.